Alternatives to Criminal Conviction in a Comparative Analysis of Positive Law and Islamic Criminal Law - Fauzan, Fauzan (Institut Agama Islam Negeri Curup, 2022)
This paper aims to comprehensively analyze the concept of alternative punishment in a comparative study of positive law and Islamic criminal law. Currently, imprisonment is still the main choice, causing overcrowding in prisons in Indonesia. Sharp criticism and dissatisfaction with imprisonment have prompted the development of alternative punishments other than imprisonment that are in accordance with the purpose of punishment. This study is a type of qualitative research using data collection techniques through literature studies. The data used in this study was taken from secondary data from various literatures consisting of books, journals, mass media, news, social media related to alternative sentencing. The conclusion of this paper shows that in positive law, alternative provisions for punishment other than imprisonment have been regulated in the Criminal Code (KUHP) and other laws and regulations, including in the form of fines (compensation), rehabilitation sanctions for narcotics abuse cases, and settlement of criminal cases outside the court (APS) by prioritizing the principle of restorative justice, namely peace and forgiveness, for the perpetrators, victims and the community. In positive law, alternative punishment has an ideal concept with the aim of sentencing that leads to recovery, not retaliation. This paper also concludes that in the concept of Islamic criminal law, the provision of alternative punishments contains the principles in maqashid sharia, namely in maintaining religion (al-dÃ®n), soul (al-nafs), offspring (al-nasl), property (al-mÃ¢l) and reason (al-aql).